Cardiac hypertrophy and structural and metabolic remodeling related to seasonal dormancy in the first annual cycle in tegu lizards - Silveira, Lilian Cristina da; Nascimento, Lucas Francisco R. do; Colquhoun, Alison; Abe, Augusto S. [UNESP]; Souza, Silvia Cristina R. de (Elsevier B.V., 2013)
Morpho-functional adjustments in the heart of juvenile tegu lizards (Tupinambis merianae) were analyzed at distinct seasonal periods to investigate how the demands of growth and of energy saving are reconciled during the first annual cycle. The relative ventricular mass (Mv) was 31% and 69% larger in late autumn and winter dormancy, respectively, compared to early autumn. This effect did not persist during unfed arousal, suggesting that protein accumulates in the heart during hypometabolism and is degraded on arousal. Both the hypertrophy and the atrophy were disproportionate in the largest individuals. In contrast, Mv was smaller in lizards that were starved during spring activity compared to fed lizards, this effect being larger in smaller individuals. In late autumn and winter dormancy the spongy myocardium had 8% of the section area covered by lacunary spaces, which expanded after food intake during arousal and reached 29% in spring activity together with higher density of cardiomyocytes. Total and soluble proteins per mass unity were unchanged, and maximum activities of selected enzymes suggest sustained glycolytic and aerobic capacities during hypometabolism. Results indicate that important structural adjustments occur in the heart in anticipation of dormancy, and that the protein balance in the tissue is maintained at winter temperatures similar to 17 degrees C. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Metabolism; Cardiac hypertrophy; Seasonal dormancy; Myocardium; Tupinambis merianae